Nonionic surfactants based on amphiphilic polyphosphonate copolymers prepared via anionic ring-opening copolymerization. (15th May 2020) - Rheinberger, Timo; Wolf, Thomas; Wurm, Frederik R.
Graphical abstract: Amphiphilic polyphosphonate copolymers were prepared by anionic ring-opening polymerization of the novel 2- n -dodecyl-2-oxo-1, 3, 2-dioxaphospholane and 2-ethyl-2-oxo-1, 3, 2-dioxaphospholane. Well-defined copolymers with adjustable comonomer contents and surface-active properties were prepared that can be used to stabilize emulsions. Highlights: Novel monomer 2- n -dodecyl-2-oxo-1, 3, 2-dioxaphospholane for anionic ring-opening polymerization. Amphiphilic copolyphosphonates prepared with adjustable surfactant properties. Nonionic surfactants effectively stabilize direct and inverse emulsions. Nonionic polyphosphonate-surfactant used to prepare well-defined polymer nanoparticles by miniemulsion polymerization. Abstract: Nonionic surfactants are omnipresent in our everyday life and used in modern drug delivery. The synthesis of degradable surfactants is crucial to simplify the purification of final products or reduce polymer waste. Here, we present the synthesis of a new amphiphilic 2- n -dodecyl-2-oxo-1, 3, 2-dioxaphospholane, a monomer for the anionic ring-opening polymerization towards poly(ethylene alkyl phosphonate)s. The novel monomer is copolymerized with 2-ethyl-2-oxo-1, 3, 2-dioxaphospholane to produce well-defined, water-soluble, and surface-active copolymers with molar masses up to 18, 400 g mol −1, dispersities between 1.2 and 1.3, and critical aggregation concentrations below 0.07 g L −1 . The reactivity ratios of the two comonomers indicate a random monomer incorporation with r 1  = 1.46 and r 2  = 0.68. Adjusting the comonomer ratio changes the amphiphilicity of the resulting copolymers. They are applied in the free radical miniemulsion polymerization to produce well-defined nanoparticles. The intrinsic hydrolytic degradability of polyphosphonates makes these polymers interesting candidates for use in, emulsion stabilization for drug delivery or cosmetics.